Trends in African Migration to Europe: Drivers Beyond Economic Motivations. (September 2019) - Giménez-Gómez, José-Manuel; Walle, Yabibal M.; Zergawu, Yitagesu Zewdu
The current migration and refugee crisis in Europe requires an understanding of the different migration drivers beyond the well-known economic determinants. In this article, we view migration from a broader human security perspective and analyze the determinants of regular and asylum seeker migration flows from Africa to Europe for the period 1990 to 2014. Our results show that, in addition to economic determinants, a combination of push and pull factors influences migration decisions of individuals. In particular, rising political persecution, human rights violations, ethnic tensions, political instability, and civil conflicts in African source countries are all significantly associated with increased migration flows into European destination countries. Therefore, our results underscore the need for the European Union and European countries to collaborate with the source countries, not only in terms of supporting economic development in the source countries but also in promoting human security: human rights, democracy, peace, and social stability.